Discourse Analysis and the Problem of Translation Equivalence - Lotfipour-Saedi, Kazem (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1990)
AbstractThe translator's task has usually been defined as the establishment of an equivalence between the source language (SL) and the target language (TL) texts, and the translation process has been characterized as a branch of contrastive linguistics. But neither the nature of translation equivalence (TE) has been carefully specified nor a comprehensive framework consistent with the true nature of linguistic I communicative behaviour has been employed for contrasting languages for translation purposes. Consequently translation studies have always lacked a sound scientific framework.This paper attempts to study the nature of TE within the framework of a comprehensive contrastive analysis of SL and TL at discourse level and suggests seven different components for TE.